Effect of temperature on the fracture toughness of wood under mode I quasi-static loading - Dourado, N. (2019)
A numerical and experimental study was performed to evaluate the critical strain energy release rate of wood under mode I loading (GIc), in the range of 30 C and 110 C. Pinus pinaster Ait. was employed as testing material, using the double cantilever beam (DCB) test, promoting fracture in the RL fracture sys- tem. The determination of Resistance-curves was accomplished using an equivalent crack length method, which does not require crack length measurement in the course of the experimental test. This aspect was found crucial since wood develops a non-negligible fracture process zone (FPZ) ahead of the crack tip, and the experiments required the use of a climate chamber with limited dimensions for visual access. It was observed that the critical energy release rate is affected by temperature within the referred range. Cohesive laws were also determined to replicate the experimental response as a function of the tested temperatures.